Case Report: A homozygous selenocysteine insertion sequence-binding protein 2 (SECISBP2) gene mutation in a pediatric patient - Almohammadi, Lina; Alsayel, Lama; Aljumaa, Mohammad; Alhuthil, Raghad; Alsagheir, Afaf (Frontiers in Pediatrics, 2025)
Selenocysteine insertion sequence-binding protein 2 (SECISBP2) is crucial for the biosynthesis of selenoproteins, including iodothyronine deiodinases, which play a vital role in thyroid hormone metabolism. Mutations in SECISBP2 can disrupt thyroid function, leading to various clinical manifestations across multiple systems. We present the case of a 3-year-old Saudi female who was referred for genetic testing due to poor growth, developmental abnormalities, and notable facial dysmorphism. Laboratory tests indicated elevated FT4 levels, low T3 levels, and modestly elevated TSH values. Whole-exome sequencing revealed a homozygous pathogenic variant in the SECISBP2 gene (c.358C>T; p.Arg120Ter), correlating with the laboratory findings and the patient's clinical presentation. Additional variants of uncertain significance (VUS) in the ARCN1 and DNA2 genes were also identified but were considered clinically insignificant due to inheritance patterns and the absence of corresponding phenotypes in heterozygous family members. Treatment with liothyronine (L-T3) led to significant clinical improvement in growth and energy levels over a two-year follow-up period. This case highlights the importance of identifying the specific biochemical profile associated with SECISBP2 deficiency and advocates for the inclusion of SECISBP2 in genetic testing panels for endocrine and neurodevelopmental disorders to prevent diagnostic delays. The therapeutic efficacy of liothyronine in such cases is further supported.